THE IMPACT OF AN INTEGRATED TRANSPORT NETWORK ON URBAN DEVELOPMENT IN LAO PDR - SAUVALY, Vivath (Nakhara : Journal of Environmental Design and Planning, 2007)
This paper examines urban development in the Lao People’s Democratic Republic that links to the improvement of the Greater Mekong Sub-region integrated land transport network. My objective is to measure the extent to which the urban structure has been changed as the result of the improvement of the integrated land transport network during the last three decades. A time-series analysis and associated indicator called ‘the integrated land transport development phases’ has been used to understand the evolution of the transport network itself and to identify correlation between integrated land transport network and urban development. The integrated land transport development phases reflect the degree to which the Lao PDR has integrated into the international community; and if this has been dependent on the improved cross border facilities and the improved land-linked transport network. The integration effort of the Lao PDR associated with the improvement of the Greater Mekong Sub-region integrated land transport network can be divided into four distinctive stages. Each stage has its own features attributable; and that link to the variables of the improved cross border facilities, and the improved land-linked transport network in each period. The analysis revealed that the population agglomeration and urban development was closely correlated to improvement of the integrated land transport network in each time frame. Results of the analysis showed that the integrated land transport network has impacted on economic growth and also the population agglomeration and urban development process in the Lao PDR. The improved integrated land transport network has accelerated economic growth of the country as well as provided equal economic opportunities across the country. This is reflected through an equitably increasing annual population growth rate throughout the country during the last three decades. The outcomes of this research certainly reflects the effectiveness of the Greater Mekong Sub-region initiatives in relation to policies, agreements, infrastructure and services supporting increased cross border trade and tourism. The efforts towards strengthening regional economic cooperation as such are also especially important for the development of the NorthSouth and East West Economic Corridors (NSEC and EWEC).